2006
DOI: 10.1299/jsmeb.49.1111
|View full text |Cite
|
Sign up to set email alerts
|

Plane Offset Jet Discharged into Water of Finite Depth

Abstract: A plane submerged turbulent water jet discharged parallel to the offset bottom wall in a channel with a finite water depth was investigated experimentally. Depending on the depth of the nozzle and its height from the bottom, the jet deflects towards either of two boundaries, the free surface or the solid wall. Detailed data on the velocity field measured by the Particle Image Velocimetry (PIV) method are obtained to examine the effect of the opposite boundary on the deflecting jet and the difference in the jet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Similar diagrams with figures 12(a) and (b) were obtained in experiments by Sudo et al (1998), Shimada et al (2004) and Tsunoda et al (2006) although their experiments were performed at much larger Reynolds numbers such as Re = 4430-177 00 (Sudo et al 1998, Shimada et al 2004 and Re = 2500 (Tsunoda et al 2006) and the length of the channel (L in figure 1) was much longer. They concluded that the direction of deflection of the flow is determined solely by the values of h 1 and h 2 , independently of the Reynolds number, and they attributed the mechanism of deflection to the Coanda effect.…”
Section: Effect Of the Height Of The Inlet Throatsupporting
confidence: 85%
See 2 more Smart Citations
“…Similar diagrams with figures 12(a) and (b) were obtained in experiments by Sudo et al (1998), Shimada et al (2004) and Tsunoda et al (2006) although their experiments were performed at much larger Reynolds numbers such as Re = 4430-177 00 (Sudo et al 1998, Shimada et al 2004 and Re = 2500 (Tsunoda et al 2006) and the length of the channel (L in figure 1) was much longer. They concluded that the direction of deflection of the flow is determined solely by the values of h 1 and h 2 , independently of the Reynolds number, and they attributed the mechanism of deflection to the Coanda effect.…”
Section: Effect Of the Height Of The Inlet Throatsupporting
confidence: 85%
“…Multiple stable states of flow through the reservoir with a free surface were found in experiments by Shimada et al (2004) and confirmed by Tsunoda et al (2006), which was unexpected because the flow was thought to be determined uniquely for such an asymmetric configuration. We traced the origin of the multiple flows up to the pitchfork bifurcation of flow in a symmetric channel with two rigid boundaries by using polymorphic transformations.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…An offset jet with small offset ratio has also been studied previously by Lund (1986). The flow field of a plane offset jet that discharges between a free surface and a solid wall was investigated experimentally by Tsunoda et al (2006). Miozzi et al (2010) also worked on a plane offset jet that discharges in the free surface surrounding fluid.…”
Section: Introductionmentioning
confidence: 99%